Jacques de Morgan et André Jouannin : les premières recherches archéologiques de la France au Bahreïn - Nicole Chevalier (Arabian Humanities)
In September 1903, during a stopover of a few days in Bahrain, André Jouannin carried out a short exploration in the A'ali necropolis. In 1905, although succinct, the results were published under the direction of Jacques de Morgan in the Mémoires de la Délégation Scientifique Française en Perse. By including this research among the work of the Delegation, Morgan showed his interest in the study of necropolises and his desire to extend the skills to the Gulf.